On natural law as a possible normative reference point in legislative processes - Bogdan Szlachta (Chrześcijaństwo-Świat-Polityka)
In the modern era, the only indicator of the validity of law is that it is passed by the authorities in accordance with procedures. Has the classical theory of natural law ceased to matter? The author, referring to contemporary statements of popes and documents of the Catholic Church, analyses what significance natural law has today from a normative point of view and why it is particularly important in the present-day world, as well as in a multicultural world.